2022
DOI: 10.1186/s12887-022-03407-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and duration of extreme hypoxemic and hyperoxemic episodes during manual and automatic oxygen control in preterm infants: a retrospective cohort analysis from randomized studies

Abstract: Objective Neonatal exposure to episodic hypoxemia and hyperoxemia is highly relevant to outcomes. Our goal was to investigate the differences in the frequency and duration of extreme low and high SpO2 episodes between automated and manual inspired oxygen control. Design Post-hoc analysis of a cohort from prospective randomized cross-over studies. Setting Seven tertiary care neonatal intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In our study, the reduction in total percentage of time in severe hyperoxaemia (SpO 2 >98%) was largely due to a significant reduction in percentage of prolonged episodes of SpO 2 >98%. This has been reported with another A-FiO 2 system 15. Hyperoxaemia when in supplemental oxygen is largely preventable by rigorous manual adjustments of FiO 2 .…”
Section: Discussionmentioning
confidence: 64%
“…In our study, the reduction in total percentage of time in severe hyperoxaemia (SpO 2 >98%) was largely due to a significant reduction in percentage of prolonged episodes of SpO 2 >98%. This has been reported with another A-FiO 2 system 15. Hyperoxaemia when in supplemental oxygen is largely preventable by rigorous manual adjustments of FiO 2 .…”
Section: Discussionmentioning
confidence: 64%
“…The time spent in hypoxaemia (<80% SpO 2 ) was about 50% lower in the automated oxygencontrolgroupthanmanualgroup.Thetimespentinhyperoxaemia(>98%SpO 2 )wasreducedbyabout66%. 10 Abdo et al's systematic review of 13 studies confirmed these findings.Automatedoxygencontrolincreasedthetimespentwithin theSpO 2 targetsofboth85%-96%and90%-95%.Inaddition,time inhypoxaemia(SpO 2 < 80%)decreasedinthepredeterminedtarget rangesof85%-96%and90%-95%.Theautomatedcontrolsystem also reduced the time in hyperoxia (>98%) at an intended target range of 90%-95% SpO 2 . They concluded that automated oxygen delivery was rapid and effective in controlling the infants' oxygen saturation.…”
Section: E D I T O R I a Lmentioning
confidence: 82%
“…The time spent in hypoxaemia (<80% SpO 2 ) was about 50% lower in the automated oxygen control group than manual group. The time spent in hyperoxaemia (>98% SpO 2 ) was reduced by about 66% 10 …”
mentioning
confidence: 96%